Anti-fragile ICT Systems - Jørgen Hole, Kjell (Simula SpringerBriefs on Computing, 2016)
Computer Systems Organization and Communication Networks; Information Systems and Communication Service; Artificial Intelligence (incl. Robotics); Simulation and Modeling; anomaly detection, anti-fragility, cloud computing, complex adaptive systems, DevOps (Development and Operation), diversity, loose coupling